Consequences of understaffing on type of missed community care- a cross-sectional study. (December 2022) - Senek, Michaela; Robertson, Steven; Taylor, Bethany; Wood, Emily; King, Rachel; Ryan, Tony
Abstract: Background: Resource cuts to primary and community care in combination with a decline of those working in community settings is compromising quality of care and patient safety in the UK. It is reported that the negative consequences of understaffing and underfunding have worsened due to the COVID-19 pandemic. Objective: This is a cross-sectional study that aimed to examine short and long-term District and Community nursing working conditions. The objectives were to assess the prevalence of understaffing and missed care and the relationship between individual and organisational factors and their association with missed care outcome. We further explored the relationship between additional caseload, staffing levels and missed care. Methods: We developed a questionnaire based on the validated MISSCARE survey. Outcome measures were, number of vacancies per team, staffing levels, reported incidence of missed care, type of missed care, length of shift and overtime. Results: Only 23% of teams reported having no vacancies. The mean staffing ratio was reported at 60%, including agency/bank staff (0.59±1.5). Prevalence of missed care was relatively high (60%≈). The distribution of types of missed care was spread evenly across all types of nursing care. A backward stepwise regression analysis showed that the  Proportion of Permanent staff capacity OR=7.9 (95% CI 0.09-0.65), Active Caseload Size OR= 5.5 (95% CI: 1.0 – 1.003), Number of RNs on the team ( OR 4.8 (95% CI:1.003-1.058) and Amount of Overtime worked (OR = 3.9 (95% CI:0.98-1.0) variable are statistically significant predictors of missed care. The analysis showed an increase in additional allocated cases per RN as the permanent staff proportion decreased to 70%, at which point the likelihood of reported Missed Care outcome peaks. Conclusion: The compromised quality of care related to human resources and organisational aspects of the nursing process. Where RNs worked longer hours to make up for the backlog of cases, the prevalence of missed care was more likely. Longer working hours in the community increased the risk of compromised care and sub-optimal patient care. The aspects of the nursing process identified as 'missed' related to The World Health Organisation's three main pillars of community nursing (health promotion, patient education and screening). As such, significant components of the two first pillars are, according to these data, being undermined.